The Contribution of Soft leadership Skills on Organizational Change: A Study on Sudanese Insurance Companies - Ibrahim, Mohammed Mukhtar; Abker, Adam Yagoub (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the extent of the contribution of soft leadership skills on organizational change, applying it to the Sudanese insurance companies’ sector in North Kordofan State. The study problem was represented by the following main question: Does soft leadership Skills contribute to the stages of organizational change, as applied to the insurance companies’ sector in North Kordofan State? The study relied on the comprehensive enumeration method and designed a questionnaire to collect data. The descriptive approach was followed, to analyze data and test hypotheses, descriptive statistics methods were used through the Statistical Package for the Social Sciences (SPSS) program and path analysis through the (AMOS) program. The results of study showed that soft leadership skills contribute to the stages of organizational change through the dimension of preparing for change, where the level of significance reached (.000), after implementing the change, where the level of significance reached (.000), and after stabilizing the change, where the level of significance reached (.000). The study recommended that insurance company managements practice soft leadership skills and encourage employees to feel responsible for implementing organizational change in order to develop their companies to keep pace with the rapidly changing environment.